2020
DOI: 10.31557/apjcp.2020.21.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Response to Neoadjuvant Chemotherapy Using 18F FDG PET-CT in Patients with Locally Advanced Breast Cancer

Abstract: Objective:The study was aimed to find the utility of 18F FDG PET CT in assessing response to neoadjuvant chemotherapy (NACT) in female patients with locally advanced breast cancer (LABC). Methods: All willing women with biopsy proven LABC, following clinical evaluation underwent baseline 18F FDG PET CT along with mammosonograpy and contrast enhanced computerized chest radiography (CECT). The response was assessed clinically before each cycle of chemotherapy using RECIST criteria. Those who were progressing cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Regarding regional lymph node staging, FDG PET-CT has higher accuracy than other imaging techniques [ 58 ]. It was also demonstrated that the use of FDG PET-CT changed the initial staging and therapy and is helpful in the surveillance of neoadjuvant chemotherapy [ 58 , 60 ]. Using PET-CT after neoadjuvant chemotherapy can avoid radical mastectomy, detecting the presence of residual neoplasia better than MRI [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding regional lymph node staging, FDG PET-CT has higher accuracy than other imaging techniques [ 58 ]. It was also demonstrated that the use of FDG PET-CT changed the initial staging and therapy and is helpful in the surveillance of neoadjuvant chemotherapy [ 58 , 60 ]. Using PET-CT after neoadjuvant chemotherapy can avoid radical mastectomy, detecting the presence of residual neoplasia better than MRI [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Hulikal et al demonstrated that PET/CT was more accurate (87%) than clinical assessment (39%) and CT (56%) for response evaluation [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…This shows that these parameters should always be taken into account for the construction of reliable predictive models, because of their well-known importance. Most of the PET/CT studies for the prediction of the treatment response in breast cancer do not include radiomic analysis, and they have been performed in a neoadjuvant context [ 34 , 35 ]; only a few studies consider the treatment response in patients with metastatic cancer [ 6 , 36 ]. On the other hand, concerning the existing PET/CT radiomic studies in breast cancer, they have only considered a neoadjuvant context [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%